A relational perspective on supervisor-initiated turnover: Implications for human resource management based on a multi-method investigation of leader–member exchange relationships - Laura Becker; Elias Ertz; Marion Büttgen (Human Resource Management, 2022)
Despite the great emphasis organizations and human resource management (HRM) research place on turnover issues, one turnover phenomenon has received only limited attention so far: joint leader–member turnover. This research examines supervisor-initiated turnover (SIT) (i.e., employees' decision to quit their employer to follow a former supervisor to a new organization) and develops a comprehensive model of the SIT decision process, grounded on conservation of resources (COR) theory, that delineates the resource evaluation, conservation and investment deliberations of employees. We take a relational perspective and particularly focus on the leader–member relationship as an important antecedent of SIT and thereby respond to the call for more critical investigations of leader–member exchange (LMX) and corresponding HRM implications. Our three studies (survey, scenario experiment, and dyadic interview study) demonstrate that LMX positively affects SIT intentions (SITI) and that supervisor commitment represents an important mediating mechanism of the LMX–SITI relationship. Our interview study with 46 leader–member dyads identifies relational factors that promote or hinder SIT beyond the leader–member relationship. We discuss the theoretical contributions and practical implications for HRM.
Keywords: 650; commitment; COR theory; LMX; supervisor-initiated turnover intention; voluntary turnover